2021
DOI: 10.1007/s00701-021-04954-5
|View full text |Cite
|
Sign up to set email alerts
|

Motor and functional outcome of selective dorsal rhizotomy in children with spastic diplegia at 12 and 24 months of follow-up

Abstract: Background Selective dorsal rhizotomy (SDR) in ambulatory children affected by cerebral palsy (CP) is a surgical treatment option to lower spasticity and thereby improve gait and ambulation. The aim of the current study is to investigate the outcome of children with respect to spasticity, muscle strength, and overall function after SDR. Methods All children who underwent SDR via a single-level laminotomy in the time period from January 2007 to Apri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…There is no doubt that SDR is very efficient in decreasing spasticity in children with CP ( 64) but the true effects on motor function were also difficult to interpret. The results of the present study confirm that this surgery can produce important gains in gross motor function with a mean GMFMER of 6.5 (31,34,38,(46)(47)(48)(49)(50)(51)(52)(53). In this case the GMFMER value demonstrate a particularly beneficial effect of the treatment, because it applies on a long period, twelve months in most studies (64).…”
Section: Discussionsupporting
confidence: 80%
“…There is no doubt that SDR is very efficient in decreasing spasticity in children with CP ( 64) but the true effects on motor function were also difficult to interpret. The results of the present study confirm that this surgery can produce important gains in gross motor function with a mean GMFMER of 6.5 (31,34,38,(46)(47)(48)(49)(50)(51)(52)(53). In this case the GMFMER value demonstrate a particularly beneficial effect of the treatment, because it applies on a long period, twelve months in most studies (64).…”
Section: Discussionsupporting
confidence: 80%
“…A recent study has suggested that the benefits of SDR relating to quality of life, and muscle strength, are maintained after SDR [27]. Another study suggested that the benefit of SDR in GMFCS II and III patients increased between 12 and 24 months, with a greater degree of improvement seen [17,19]. Even if SDR is not successful by measured criteria, the vast majority of patients still report improved functioning, even if this was not quantifiable [28].…”
Section: Discussionmentioning
confidence: 99%
“…Smaller, single-center studies have suggested that these patients may also benefit from SDR [ 14 , 15 ], although this has yet to be confirmed by larger, prospective studies, and the exact magnitude of the benefit obtained relative to ambulatory patients is also unclear. The effect on quality of life, motor, and spasticity outcomes has been indicated to be favorable [ 16 ], with an increase in gross motor function and spasticity, but there is a need for prospective evidence of this association [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another treatment used to alleviate spasticity in children with cerebral palsy is rhizotomy. Studies have shown that performing selective dorsal rhizotomy at a young age can reduce the need for orthopedic surgery [48]. Goals of rhizotomy are decreased tone, increased mobility, and the facilitation of care for the patient; however, the reduction in spasticity cannot be predicted and sometimes results in excessive hypotonia [49].…”
Section: Neurosurgical Approachesmentioning
confidence: 99%